Family planning field workers in Bangladesh as influence agents: some policy implications - Andaleeb, Syed Saad (© Department of Health Policy and Administration, School of Public Health University of North Carolina, 2016)
This is an Open Access Article. It is published by The Journal of Health and Population in Developing Countries (ISSN 1095-8940) is a publication of the Department of Health Policy and Administration, School of Public Health University of North Carolina at Chapel Hill.